2017
DOI: 10.1111/nhs.12339
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effectiveness of two different interventions to reduce preoperative anxiety: A randomized controlled study

Abstract: This study was conducted to determine and compare the effectiveness of nature sounds and relaxation exercises for reducing preoperative anxiety. A repeated measures randomized controlled trial design was used. We divided 159 preoperative patients into three groups: nature sounds (n = 53), relaxation exercises (n = 53), and control groups (n = 53). We evaluated anxiety using the visual analog scale and state anxiety inventory scores immediately before, immediately after, and 30 min after interventions in nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 38 publications
1
29
0
7
Order By: Relevance
“…The findings of this study demonstrated that Benson's relaxation method reduces preoperative trait anxiety in patients undergoing cataract surgery. These results are consistent with those reported by other researchers (5,12).…”
Section: Discussionsupporting
confidence: 94%
“…The findings of this study demonstrated that Benson's relaxation method reduces preoperative trait anxiety in patients undergoing cataract surgery. These results are consistent with those reported by other researchers (5,12).…”
Section: Discussionsupporting
confidence: 94%
“…Prevention of anxiety, both from the patient and caregivers' perspective, was the most common primary outcome of interest, accounting for over a fifth of studies (n=20, 23%). 32,37,38,49,53,54,57,58,59,63,70,71,79,81,91,93,94,103,105,108 Prevention of anxiety was a secondary outcome of interest in a further nine (10%) studies. 22,23,25,47,50,55,69,73,80 Of the studies including anxiety prevention as the primary outcome, nine studies (47%) were focused on adult patients; 32,38,53,57,59,71,81,94,105 nine were focused on pediatric patients, 37,49,54,63,79,91,93,103,108 (with four of these also including caregivers as a sub-population, …”
Section: Prevention Of Caregiver and Patient Anxietymentioning
confidence: 99%
“…22,23,25,47,50,55,69,73,80 Of the studies including anxiety prevention as the primary outcome, nine studies (47%) were focused on adult patients; 32,38,53,57,59,71,81,94,105 nine were focused on pediatric patients, 37,49,54,63,79,91,93,103,108 (with four of these also including caregivers as a sub-population, 37,49,54,108 and another focused on adolescents 37 ); one study concentrated solely on caregiver (parent) anxiety. 70 The interventions of interest included music; 32,58,59,71,103 education (including videos); 37,70,81,94 visiting preoperative facilities; 54 play; 79,91,93,108 relaxation and sounds from nature; 57 aromatherapy; 53 photographic displays;…”
Section: Prevention Of Caregiver and Patient Anxietymentioning
confidence: 99%
“…Authors suggested future studies to combine music intervention with other nonpharmacologic methods considered apt to decrease sympathetic and increase parasympathetic nervous system activity. Ertuğ, N., Ulusoylu, Ö, Bal, A., & Özgür, H. (2017)…”
Section: Appendix A-3 Appendix A-4mentioning
confidence: 99%
“…Limitation: anesthetic drugs influence HRV values. Author Ertuğ, N., Ulusoylu, Ö, Bal, A., & Özgür, H. (2017).…”
Section: Appendix A-3 Appendix A-4mentioning
confidence: 99%